Design, Repeatability, and Comparison to Literature Data of a New Noninvasive Device Called "Rotameter" to Measure Rotational Knee Laxity. (28th June 2015) - Neumann, Simon; Maas, Stefan; Waldmann, Danièle; Ricci, Pierre-Louis; Zürbes, Arno; Arnoux, Pierre-Jean; Kelm, Jens
Abstract : The present paper deals with the design, the repeatability, and the comparison to literature data of a new measuring device called "Rotameter" to characterize the rotational knee laxity or the tibia-femoral rotation (TFR). The initial prototype P1 of the Rotameter is shortly introduced and then modified according to trials carried out on a prosthetic leg and on five healthy volunteers, leading therefore to an improved prototype P2. A comparison of results obtained from P1 and P2 with the same male subject shows the enhancements of P2. Intertester and intratester repeatability of this new device were shown and it was observed that rotational laxities of left and right knees are the same for a healthy subject. Moreover, a literature review showed that measurements with P2 presented lower TFR values than other noninvasive devices. The measured TFR versus torque characteristic was quite similar to other invasive devices, which are more difficult to use and harmful to the patient. Hence, our prototype P2 proved to be an easy-to-use and suitable device for quantifying rotational knee laxity. A forthcoming study will validate the Rotameter thanks to an approach based on computed tomography in order to evaluate its precision.